Life skills education: a coping strategy against substance abuse - Roy, Pritam Kumar; Pydipalli, Mounika; Trivedi, Shruti; Rehman, Waheda; Thakkar, Vallabh (International Journal Of Community Medicine And Public Health, 2021)
Substance abuse has been a topic of discussion for healthcare professionals. It involves using harmful or hazardous psychoactive substances that, if administered into one’s system, can affect the mental processes. Consumption of these substances leads to societal as well as health problems among its users there by indirectly affecting their families too. These substances mainly include alcohol, tobacco, opiates, cocaine, amphetamines, hallucinogens, prescription and over-the-counter drug abuse.1,2 According to the world drug report 2020 by United Nations Office on Drugs and Crime (UNODC), there are about 35 million people who suffer from drug use disorders and require treatment services globally.2 In India, the substance abuse epidemic in the younger generation has increased rapidly. The crucial factors which lead to these problems involve familial, social as well as individual problems. Familial issues may involve childhood maltreatment or familial substance abuse. Similarly, social issues involves deviant peer pressure and association with popular groups in order to prevent from being bullied. Individual factors which might lead to substance abuse includes depression and attention deficit hyperactivity disorder (ADHD).3 Its prevalence at the national level varies for different substance abuse forms, accompanied by drastic regional variations. Issues regarding treatment access and adherence concerning substance user disorders (SUD) already existed. Due to the current COVID-19 situation, drastic social and economic changes have further worsened the situation. So in this regard, newer strategies have to be brought up in place.4 It has been found that life skills education is one of the most influential activities in school-based substance abuse prevention.